The islamic influence on Saadia Gaon’s method in defending Rabbinic Judaism - Ali, Walid Reda; Abo-Elmagd, Lila; Eldin, Ahmad Abdel Tawwab Sharaf (Penerbit Universiti Kebangsaan Malaysia, 2024)
Saadia Al-Fayyumi was one of the medieval scholars of Jewish law who lived in Muslim societies. He was the first in Iraq to defend Rabbinic Judaism against the opponents and skeptics of its religious heritage and he was influenced in his defense by Islamic thought. Previous studies discussed Saadia’s defense of the Written and Oral law and illustrated Saadia’s polemical writings against the Karaites. The current paper discusses the influence of Islam on Saadia’s method in defending Rabbinic Judaism. Also, this essay illustrates the influence of Islamic thought on Saadia’s arguments to pave the way for the Rabbis to use reason like the Mu’tazilah to defend their beliefs and provided them with arguments and proofs. Clearly, Islamic thought was a principle for Saadia to establish the foundations of faith. He laid down the principles of faith just as the Mu’tazilah and was influenced by Mu’tazilah’s thoughts, Muslim jurists, Islamic theological doctrines, and their various ideas related to religious matters. Also, Saadia agreed with the Islamic theological sects in using logical evidences and religious texts as defensive tools to defend his beliefs. This Islamic influence on Jewish thought was a factor in its development, especially in light of the Arab-Islamic civilization in the medieval ages between 10th and the 15th centuries CE.